StELIUM: A student experiment to investigate the sloshing of magnetic liquids in microgravity. (August 2020) - Romero-Calvo, Á.; García-Salcedo, A.J.; Garrone, F.; Rivoalen, I.; Cano-Gómez, G.; Castro-Hernández, E.; Herrada Gutiérrez, M.Á.; Maggi, F.
Abstract: Liquid sloshing represents a major challenge for the design and operation of space vehicles. In low-gravity environments, a highly non-linear movement can be produced due to the lack of stabilizing forces. This gives rise to significant disturbances that impact on the propulsion and attitude control systems of the spacecraft. The employment of magnetically susceptible fluids may open an interesting avenue to address this problem, but their dynamics in low gravity remain practically unexplored. The UNOOSA DropTES StELIUM project aims at filling this gap by studying the lateral sloshing of a ferrofluid solution subjected to an inhomogeneous magnetic field in microgravity. This paper describes the design process, challenges and preliminary results of the experiment, which was successfully launched at ZARM's drop tower in November 2019. The outcomes will be employed to validate the quasi-analytical models developed by the authors and set the path for the design of magnetic propellant positioning devices in space. Highlights: The StELIUM project studies the lateral sloshing of ferrofluids in microgravity. The experiment setup and drop tower campaign of StELIUM are described. A dedicated surface reconstruction system is successfully designed and tested. For the first time, a torque-generating setup is launched at ZARM's drop tower. Sloshing control with magnetic liquids may apply to future space technology.